Examining the gaps in perinatal mental health care: A qualitative study of the perceptions of perinatal service providers in Canada - DeRoche, Christina; Hooykaas, Amanda; Ou, Christine; Charlebois, Jaime; King, Krista (Frontiers in Global Women's Health, 2023)
In Canada, access to perinatal mental health services is disparate across districts, regions, provinces, and territories. Questions remain as to how these gaps are being experienced by Canadian service providers and clinicians. This paper examines three key questions: 1) What are the experiences of care providers with respect to the screening, identifying, and managing of perinatal mental health disorders? 2) What gaps in perinatal mental health care have been identified? and 3) What unique approaches have been taken by providers, communities, and regions in addressing the needs of their populations? To address these questions, 435 participants from across Canada were surveyed using an online survey constructed by the research members of the CPMHC. A qualitative analysis of the data revealed three key themes: groups marginalized by the current perinatal mental health system, gaps in services from community-led initiatives; and systemic and policy issues. It is within these three themes that this study identifies key components needed in a national approach to perinatal mental health disorders. We identify key resources that could be utilized to create policy change and provide recommendations for change.